Policies and Strategy of the Ministry of Religion in Improving Services as a Response to the Spread of Covid-19 in 2020 - Azizah Luthfiah; Rosmawati (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
The existence of the MORA in governance in Indonesia is very important so that its existence has been present throughout Indonesia with various forms and levels of work units. With regard to the outbreak of the Covid-19 early 2020, all government agencies, both central and regional, at all levels participated in carrying out efforts to handle the pandemic both with strategies and policies, such as refocusing activities, budget reallocation, policy making and appeals related to efforts to prevent and accelerate the handling of the spread of Covid-19. Reflecting on the massive change in the focus of activities and the focus of budgeting that occurred, which was diverted to support the acceleration of handling the pandemic, the object of planning as an activity of making decisions from various choices regarding targets and ways to be implemented in order to achieve the desired goals that are carried out systematically and continuously really needs attention. The purpose of this paper is to evaluate the efficiency of strategic stratetegi and the policy of improving the ministry's services as a response to the outbreak of the Covid-2019 pandemic. The research method used is descriptive analysis.